Symposium 9: Networked Learning and Networked Information: Symposium Introduction - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2004)
If networked learning is to become commonplace or even the norm, and government and EU policy in this area is to be achieved, then we will require provision of many resources – including published information resources – either at the desktop or through other devices using ICT affordances. The idea of a digital or virtual university can only be realised in so far as digital information resources are made available in ways that allow key stakeholders in universities to integrate them into the changing practices of HE – and as yet the integration between digital information/library services and MLEs/VLEs is poorly developed.